Plant metabolites as potential therapeutics against COVID-19 and other viral diseases - Sunil Kayesth; Ashu Chaudhary
The COVID-19 pandemic caused by the novel coronavirus (SARS-CoV-2) posed a serious threat to human health worldwide. The death toll was immense in many countries, irrespective of their advanced healthcare system. Post-COVID complications are equally challenging. It was realized that a single method to manage the COVID-19 pandemic and related outbreaks is not adequate; rather, an integrated approach which includes spreading awareness and educating masses about the disease, development of antiviral drugs and other safer drugs for symptomatic treatment of the disease, and mass vaccination is needed to manage such pandemic. Plants used in traditional medicine systems contain diverse secondary metabolites. These have been screened against SARS-CoV-2 and have shown effective antiviral activities. Many of the plant products are also useful for symptomatic treatment. The immune-boosting properties of many phytochemicals have been well documented. In this review, the potential of traditional medicinal plants for effective management of the COVID-19 pandemic is presented.